Lenalidomide in combination with dexamethasone: effective regimen in patients with relapsed or refractory multiple myeloma complicated by renal impairment - Klein, Ulrike; Neben, Kai; Hielscher, Thomas; Heiß, Christiane; Ho, Anthony Dick; Goldschmidt, Hartmut (Annals of hematology, 2011)
Over the past decade, treatment options for patients with multiple myeloma (MM) have improved substantially, resulting in better response rates and prolonged overall survival (OS). Nevertheless, MM remains a challenging disease, especially if renal insufficiency (RI) or extensive pre-treatment aggravates the assignment of the optimal treatment schedule. In this retrospective study, we analyzed the outcome of lenalidomide plus dexamethasone in 167 patients with relapsed or refractory MM with focus on RI. The baseline creatinine clearance (CLCr) was normal in 94 patients (CLCr ≥ 80 ml/min), while RI was observed in 73 patients, including 40 patients with mild RI (50 ≤ CLCr < 80 ml/min) and 33 patients with moderate or severe RI (CLCr < 50 ml/min). Response rates declined depending on the severity of RI, being 67% among patients with normal kidney function, 60% among patients with mild RI and 49% among patients with moderate or severe RI. Time to progression (TTP) was significantly reduced in patients with severe RI and in case of >2 previous treatment lines. OS was not significantly different between patients with normal and impaired renal function. In contrast, the number of previous treatment lines (2 vs. <2) and the use of novel agents like bortezomib or thalidomide prior to lenalidomide plus dexamethasone therapy had a more adverse effect on OS. In conclusion, lenalidomide plus dexamethasone is an effective regimen for relapsed or refractory patients with MM complicated by RI with manageable toxicity.
Published online: 21 September 2010
Gesehen am 18.08.2022